Preclinical Science Regarding Cannabinoids as Analgesics: An Overview - ME Lynch (Pain Research and Management)
Modern pharmacology of cannabinoids began in 1964 with the isolation and partial synthesis of delta-9-tetrahydrocannabinol, the main psychoactive agent in herbal cannabis. Since then, potent antinociceptive and antihyperalgesic effects of cannabinoid agonists in animal models of acute and chronic pain; the presence of cannabinoid receptors in pain-processing areas of the brain, spinal cord and periphery; and evidence supporting endogenous modulation of pain systems by cannabinoids has provided support that cannabinoids exhibit significant potential as analgesics. The present article presents an overview of the preclinical science.